Percepcyjna cecha smaku w strukturze definicji słownikowych (na podstawie słowników języka polskiego) - Yodlovska, Alina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*65.77px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998);" role="presentation">The article compares the verbal description <span dir="ltr" style="left: calc(var(--scale-factor)*240.57px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99148);" role="presentation">of the names of thirty-four fruits in Polish <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01055);" role="presentation">dictionaries, taking into <span dir="ltr" style="left: calc(var(--scale-factor)*164.54px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00994);" role="presentation">account the descriptions of tastes in the definitions and their <span dir="ltr" style="left: calc(var(--scale-factor)*66.27px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0336);" role="presentation">relationship with the structure of the definitions. The definitions of bases and poly<span dir="ltr" style="left: calc(var(--scale-factor)*66.31px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99548);" role="presentation">modal tastes are analysed and differences in the way they are interpreted are revealed. <span dir="ltr" style="left: calc(var(--scale-factor)*66.13px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02839);" role="presentation">Standards for the perception <span dir="ltr" style="left: calc(var(--scale-factor)*185.38px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0185);" role="presentation">of the tastes in Polish, Russian, Ukrainian and English <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99393);" role="presentation">are highlighted.